Anatomic landmarks of the glossopharyngeal nerve: A microsurgical anatomic study - Özveren, MF; Türe, U; Özek, MM; Pamir, MN (Lippincott Williams & Wilkins, 2003)
OBJECTIVE: Compared with other lower cranial nerves, the glossopharyngeal nerve (GPhN) is well hidden within the jugular foramen, at the infratemporal fossa, and in the study aim's to disclose the course of the GPhN and point deep layer of the neck. This. out landmarks to aid in its exposure. METHODS: The GPhN. was studied in 10 cadaveric heads (20 sides) injected with colored latex for microsurgical dissection. The specimens were dissected under the surgical microscope. RESULTS: The, GPhN can be divided into three portions: cisternal, jugular foramen, and extracranial. The rootlets of the GPhN emerge from the postolivary sulcus and course ventral to the flocculus and choroid plexus of the lateral recess of the fourth ventricle. The nerve then enters the jugular foramen through the uppermost porus (pars nervosa) and is separated from accessory nerves by a fibrous crest. The cochlear aqueduct opens to the roof of the vagus And this porus. On four sides in the cadaver specimens (20%), the GPhN traversed a separate bony jugular for amen; no separate canal was found in the other cadavers. In all canal within the specimens, the Jacobson's(tympanic) nerve emerged from the inferior ganglion of the GPhN, and the Arnold's (auricular branch of the vagus) nerve also consisted of branches from the GPhN. The, GPhN exits from the jugular foramen posteromedial to the styloid process and the 1, styloid muscles: The last four cranial nerves and the internal jugular vein pass through a narrow space. between the transverse process of the, atlas (Cl) and the styloid process. The styloid muscles are a pyramid shape, the tip of which, is formed by the attachment of the styloid muscles to the styloid process. The GPhN crosses to the anterior side of the stylopharyngeus muscle at the junction of the stylopharyngeus, middle constrictor, and hyoglossal muscles, which are at the base of the pyramid. The middle constrictor muscle forms a wall between the GPhN and the hypoglossal nerve in this region. Then, the GPhN gives off a lingual branch and deepens to innervate the pharyngeal mucosa. CONCLUSION: Two landmarks help to identify the GPhN in the subarachnoid space: the choroid plexus of the lateral recess of the fourth ventricle and the dural entrance porus of the jugular foramen. The opening of the cochlear aqueduct, the mastoid canaliculus, and the inferior tympanic canaliculus are three landmarks of the GPhN within the jugular foramen. Finally, the base of the styloid process, the base of the styloid pyramid, and the transverse process of the atlas serve as three landmarks of the GPhN at the extracranial region in the infratemporal fossa.
1st International Symposium on Microsurgical Anatomy -- OCT 04-05, 2002 -- MATSUMOTO, JAPAN
Keywords: glossopharyngeal nerve; infratemporal fossa; jugular foramen; lower cranial nerves; microsurgical anatomy; vertebral artery